Meranaw Language Vitality in Select Lanao Municipalities: A Preliminary Assessment - Alican M. Pandapatan; Sittie Aina T. Pandapatan; Basmah S. Hussain; Aisah Jamayesah A. Hadji Jamel; Norjanah U. Hadji Socor; Sittie Zinab M. Abaton; Norhamidah H. Singer; Adiah A. Ali; Isnihaya M. Ampuan; Johara D. Alangca-Azis (Universitas Negeri Semarang, 2026)
Language vitality is determined using various forms of language vitality measurements. One of these is the Expanded Graded Intergenerational Disruption Scale (EGIDS) developed by Lewis and Simons (2010). Meranaw, coded as [mrw] in Ethnologue, is a language under the Danao Language group and is reported endangered. This is seconded by a dissertation declaring it as Level 6b (threatened). Motivated by this reported language status, the researchers, who are native speakers of the said language, conducted this study to assess its vitality. Informants were selected through purposive sampling in four major divisions of the Meranaw communities. Different generations were also considered as a criterion for informant selection. The study revealed that the Meranaw language is vitally safe and is used in different domains in the province. These findings are contrary to the reported status above. The challenges perceived in language maintenance are the weakening use of language at home, influence of education and language policy, shifting language attitudes among speakers, influence of media, technology, and younger generation, migration and language attrition, and vocabulary loss. On the other hand, the initiatives reported include the home-based language initiatives, role of schools and formal education, documentation and material development, institutional and government support, and social media content creation. This entails updates on language dynamism and stability in inner and outer communities should be defined well to ensure vitality status. The study recommends another investigation using another instrument to cross-check the status of the Meranaw language.